Complementing carbon prices with carbon contracts for difference in the presence of risk: When is it beneficial and when not? - Samir Jeddi; Dominic Lencz; Theresa Wildgrube (Institute of Energy Economics at the University of Cologne (EWI), 2021)
Deep decarbonisation requires large-scale irreversible investments throughout the next decade. Policymakers discuss Carbon Contracts for Differences (CCfDs) to incentivise such investments in the industry sector. CCfDs are contracts between a regulator and a firm that pay out the difference between a guaranteed strikeprice and the actual carbon price per emission reduction generated by an investment of the firm. We develop an analytical model to assess the welfare effects of CCfDs and compare it to other carbon pricing regimes. In our model, a regulator can offer CCfDs to risk-averse firms that decide upon irreversible investments into an emission-free technology in the presence of risk. Risk can originate from the environmental damage or the variable costs of the emission-free technology. We find that a CCfD can be a beneficial policy instrument as it hedges firms' risk encouraging investments when the firms' risk aversion would otherwise inhibit this. In contrast to mitigating firms' risk by committing to a carbon price early on, CCfDs maintain the regulator's flexibility to adjust the carbon price if new information reveals. However, as CCfDs hedge the firms' revenues, they might safeguard production with the emission-free technology, even if it is ex-post inefficient. In this case, regulatory flexibility can be welfare superior to offering a CCfD.
Keywords: H23; L51; O31; Q55; Q58; 330; Climate policy; carbon pricing; risk; Carbon Contracts for Difference